Stress, Coping and Premenstrual Dysphoric Disorder in Young Pakistani Female Students - Jaffar, Sana; Safdar, Faiza; Areej, Ayesha; Khalid, Zainab; Sabir, Tayyaba (Applied Psychology Review, 2025)
The present research aimed to identify the mediating relationship between stress, coping and premenstrual dysphoric symptoms experienced by university students. A correlational research design was employed in this study. Data was collected from 15 different departments of public university. The sample consisted of 300 female students (18 to 25 years, M = 21, SD=1.16) who were experiencing symptoms of Premenstrual Dysphoric Disorder (PMDD). They were selected through purposive sampling. The Student Stress Inventory, Brief COPE and PMDD symptom tracker were employed to measure the perceived stress level, coping strategy, severity of PMDD symptoms in female university students. Correlation and regression analysis were conducted. Results of the study showed a positive relationship between stress and PMDD symptoms. Avoidant coping and PMDD symptoms were found to have a strong relationship. Coping partially mediates the relationship between stress and PMDD symptoms, highlighting its role in reducing symptom severity under high stress levels. Findings suggest that interventions targeting stress management and adaptive coping strategies may help alleviate PMDD symptoms and inform future research on tailored therapeutic approaches.